MARKETING FACTORS INFLUENCING PARENTS' DECISION MAKING TO SEND THEIR CHILDREN TO STUDY IN A SKILLS TRAINING INSTITUTES IN HAT YAI DISTRICT, SONGKHLA PROVINCE - Chaiwiwatpong, Arada; Intuluck, Watit (Dusit Thani College Journal, 2021)
This study was aimed 1) To compare parent decision variables in sending children and 2) To analyze the influence of the marketing mix on the decision of the parents to send their children to skills training institutes. The study 385 sets of questionnaires to gather information from 385 parents in Hatyai. Information gathered were used to calculate mean, percentage, standard deviation, T-Test and F-Test. Research results found that majority of parents who use the services of talent tutors are women age between 42-51 years old, single, finished bachelor’s degree, have their own business, and earn 35,000 baht per month or above. Moreover, Marketing mix have high degree of influences over their purchasing decision with a mean of 4.30. Most marketing mix factor that affect their purchasing decision is people with a mean of 4.65 with highest degree of influence, second is place with a mean of 4.47 with high degree of influence and third is process factor with a mean of 4.45 and have high degree of influence. In term of purchasing decision majority of parents focus on increasing their child’s talent in which the most important factor is 1) Need Recognition 2) Purchasing Decision 3) Post-Purchase Evaluation. Factors that affect their purchasing decision consist of process factor, physical factor, and product factor. Talent tutor owner should create strategic plan to attract the right target customers demographic and should focus on using marketing mix to improve in every aspect of their business especially people factor, place factor and process. These three factors are the most important factors that directly affect their customer’s purchasing decision and increase customer’s satisfaction altogether.